Adi Shankara’s Saundarya Lahari: A Quest of Spirituality in Devotion and Physical Body - Bhandari, Sabindra Raj (English Language Teaching Perspectives, 2022)
Saundarya Lahiri (Waves of Beauty) by Adi Shankara glorifies the Devi Shakti (power of goddess) and her physical beauty. He projects that the perfect integration of the corporal and the physical aspects lead to the zenith of spiritual realm. Therefore, Bhakti (devotion) divulges the deep veneration of Devi Shakti through Sringaric (amorous) expressions in Saundarya Lahari. It proclaims that inner evolution and the feeling of sublime in the physical beauty of Devi Shakti radiate the sublimity of the spirituality as well. As a profound poetic creation in Sanskrit, it is distinct from the established belief and religious practices, and establishes the truth that physical beauty of Shakti is also the beauty of the spiritual. To explore these dynamics of Saundarya Lahari, this article applies the qualitative approach to research and the interpretive method. It also sheds light on how the genial gravity of bhakti and physical beauty in their totality leads to the better application of critical spiritual pedagogy in teaching.